Karakteristik Sifat Mekanik Wadah Makanan dari Limbah Daun Pisang Kering - Zilmi Azyurah Rahman; Hernawati Hernawati; Ayusari Wahyuni (Universitas Islam Negeri (UIN) Mataram, 2021)
The objective of this research is to determine the physical quality of food media, consisting of small plate, large plate and small bowl. The method used of this research is testing the water absorption and resistance of the food media’s temperature. The process of making a food media using a stainless steel mold which is heated using a food thermometer with 100 and a load of 10 kg as a pressure, then it is printed for 5 minutes with 4 times taking the data for each food media. There are two testing of food media, the first test is water absorption with 29.5 for 125 miles into a small plate, 200 miles into a small bowl and 250 miles into a large plate for 60 minutes, the average value of the water absorption test for the Non-woven food media consists of three forms food medias have 0.00 as the same result, meanwhile woven media such as small plate has 65.00 , large plate has 44.83 and small bowl has 66.68 . Second test is resistance of the food medias based on temperature parameters. The temperatures used were 40, 60, 80 for non-woven food media consists of three forms food media which had few change after drying, while for woven food media consists three forms of food media had the same results, that is seepage (leaking) in the food media.